(untitled) (Research, Society and Development, 2022)
Games are directly linked to childhood and contribute to the integral development of the child. During Early Childhood Education, the child has the opportunity to explore and build artifacts, in addition to using them in pretend play contexts. In the school environment, many of these opportunities are pedagogically structured to stimulate changes in the child’s knowledge. Therefore, we have to use play as an extremely effective pedagogical resource for Early Childhood Education. In this study, we sought to understand the teaching perspective regarding the role of make-believe games in the context of Early Childhood Education. Seven teachers from the municipal Early Childhood Education network of Lavras - MG participated. These teachers were interviewed using a semi-structured script via Google Meet or WhatsApp video call. The teaching narratives were treated using the technique of discursive and intersecting textual analysis, in order to better understand the role of pretend play in Early Childhood Education. The data obtained allowed a better understanding of some existing needs within schools in relation to playing. It was also possible to verify the need for teacher training focused on practice. This could result in teachers who are more confident about their performance and more qualified to teach children.